Patterns of the use of technology by students in higher education - Aheto, Simon-Peter Kafui (Cape Peninsula University of Technology, 2017)
Rationale: Unavoidably, the 21st century is witnessing continuous discourse about students’ technology uses in higher education. This thesis explores the underpinnings of students’ technology usage in their rhizomatic (personal) learning networks in the higher educational environment through a lens of four sub-research questions and four research hypotheses. Methodology: This research adopted a cross-sectional narrative and numeric study using the Frameworks for an Integrated Methodology (FraIM). The study was conducted in four universities comprising two universities in Ghana, one in South Africa and another in Belgium. Participants and respondents included students and lecturers. Data collection methods comprise focus group interviews, individual interviews, surveys (paper and web-based) and rhizomatic maps. The philosophical underpinning was inclined towards the critical realists’ stance and hinged to Rhizome Theory and Actor Network Theory. Data were analysed through descriptive and multivariate analyses and learning analytics employing tools in social network analysis. Results were presented graphically via Rhizomatic Learning Network maps, charts, tables and narratives. Findings: Students’ personal learning networks exhibit traces of rhizomatic patterns which are related through human and non-human actors. Seven categories of actors – comprising 218 individual actors – were found in students’ Rhizomatic Learning Networks. Out of 19 traceable digital devices used by students, this research established differences among the institutions in the four most widely used digital devices: Laptop, Smartphone, Tablet or iPad, and E-Reader pro rata. Students owned, in this sequence, smartphones, laptops, tablets or iPads and e-readers. This research also found statistically significant differences among all four institutions in terms of students’ self-perceived importance of handheld mobile devices towards academic success, university wireless network experiences and satisfaction of Learning Management Systems in the universities. However, results indicated that students are not likely to skip classes when materials from course lectures are available online, implying an inclination towards a blended approach to learning despite a technologically-rich environment. Implications and Value: With an underlying effect on curriculum design and implementation, this thesis, supporting rhizomatic approaches to learning, has tremendous potential to improve personal learning networks in higher education. It further contributes an understanding of emerging patterns in the personal learning networks of higher education students within a technology-rich environment. Again, integration of the two theories – FraIM, analytical tools and style of presentation – in understanding the problem through the lens of a critical realist is novel. Key Recommendations: Further rhizoanalysis research into the detailed roles performed by individual technological actors in students’ personal learning networks in the higher educational environment is required. Additionally, clear policies exhibiting willingness and enforcement strategies to integrate technology in all facets relating to learning should guide curriculum development within the universities.
Thesis (DTech (Information Technology))--Cape Peninsula University of Technology, 2017.
Keywords: Education, Higher -- Effect of technological innovations on; Educational technology; College students -- Effect of technological innovations on